Agent-based simulation for the evaluation of a new dispatching model for the straddle carrier pooling problem. (February 2015) - Garro, Alfredo; Monaco, Maria Flavia; Russo, Wilma; Sammarra, Marcello; Sorrentino, Gregorio
To deal with several classes of planning and management problems in different business domains (transport, energy, defense, etc.) and at different decisional levels (strategic, tactical and operational levels), significant benefits can derive from the definition of solution methods which are able to combine and capitalize on the strengths of mathematical programming and agent-based techniques. In this paper, an approach based on the joint use of mathematical programming and agent-based techniques is exploited in the context of maritime logistics. In particular, a transshipment terminal is considered with the goal of planning the container transportation between the yard and the quay during the loading/discharging operations of a containership by exploiting a pool of straddle carriers shared among the quay cranes. The goal is to route the straddle carriers by determining a sequence of container movements for each of them in order to optimize a given performance criterion. In particular, a new dispatching model is proposed and evaluated through an agent-based simulation model which also made it possible a better understanding of interesting properties of the problem under consideration.